#TITLE_ALTERNATIVE# - WINDYASARI (NIM : 20511311) ;Pembimbing Prof. Dr. M. Bachri Amran, DEA, INTAN
Caffeine as aditif can be found in various products such as in foods, beverages, or pharmaceutical products in Indonesia and around the world. The most important function of caffeine is its ability in stimulating central nervous system to increase concentration and suppress drowsiness. Concomittant to the increase of caffeine usage in those daily products, there is a need to control the amount of caffeine so that the usage does not exceed maximum allowed dosage. This is to prevent the negative effect of caffeine to human body if consumed in high amount. HPLC is an analysis method that combines separation process and quantitative measurement simultaneously. Although this advantage makes it an efficient method, the operational cost is relatively high. One of the simple methods to analyse caffeine is by using UV spectrometry method since caffeine has a specific absorption around 273 nm wavelength region. However, this method requires solvent extraction process to isolate caffeine from the other components. Molecularly imprinted polymers (MIPs) are a selective polymer matrix that has ability to reversibly bind to target molecule, thus it can be used as a sorbent in the separation process. One of the most common methods to synthesize MIP is by free radical polymerization (FRP) of functional monomer in the presence of excessive cross-linker. In this study, caffeine-MIPs based on methyl-metachrylate (MMA) and ethylene glycol dimetachrylate (EGDMA) has been synthesized at temperature of 65 oC in the presence of caffeine as the template and benzoyl peroxide as the initiator. The resulted MIPs has been characterized with FTIR and SEM and compared with non imprinted polymers (NIPs). The characterization results showed an additional peak around wave number 1550 cm-1 indicating the presence of caffeine in the polymer matrix. Comparison between FTIR spectrums of NIP and MIPs showed a shift of a peak from 1633 cm-1 to 1660 cm-1 suggesting that interactions between polymer and caffeine are formed through non covalent van der Waals interaction. Binding assays of the MIPs using batch and column method with methanol-acetic acid (9:1) as solvent and monitored by UV spectrometer at wavelength of 273 nm, showed that adsorption of the caffeine on iv the polymer matrix was not affected by pH with the adsorption kinetic achieved in average of 6 min.The adsorption profile of the MIPs followed Langmuir linear curve with adsorption capacity based on experimental and calculation at least 25 mg/g and 48 mg/g respectively. The recovery value of up to 98 % was obtained by SPE method. Quantitative analysis of caffeine in health drink “Herbalife” using MIPs as sorbent gave average caffeine content of 69.41 mg/g, whereas the caffeine content shown on the packaging is 68 mg/g. The relative selectivity coefficient calculated from adsorption capacity of MIPs and NIPs is 1.09 suggesting that caffeine-MIPs is less selective. This could be due to the interactions formed are only van der Waals non covalent interaction with possibility that the caffeine template formation is not optimum. To be used as a sorbent in caffeine content analysis, further optimization to improve adsorption capacity and selectivity is required such as to use other monomer that can interact better with the target molecule or to implement different synthesis technique that can form good template.